Urgensi Isbat Nikah Sebagai Aspek Legalitas Nikah Sirri - Nurmadiah, Risti (Journal of Comprehensive Islamic Studies, 2023)
This article reveals the understanding of the people of Muara Bulian District, Batang Hari Regency regarding the impact of sirri marriage on women and children. This article comes from field research using a qualitative approach method. The types of data used are primary, secondary and tertiary data sources. Data collection was carried out through interviews, observation and documentation. Research findings show that the factors causing sirri marriages in the Muara Bulian District include; because there is no blessing from parents, to avoid committing the sin of adultery, and to avoid the burden of administrative costs. On the other hand, the reason people have not carried out the marriage isbat is because of the cost factor. Furthermore, it cannot be avoided that there is an influence of unregistered marriage on the rights of wives and children. Artikel ini mengungkap pemahaman masyarakat Kecamatan Muara Bulian Kabupaten Batang Hari akan dampak dari pernikahan sirri  pada perempuan dan anak. Artikel ini berasal dari penelitian lapangan (Field research) dengan menggunakan metode pendekatan kualitatif. Jenis data yang digunakan adalah sumber data primer, skunder, dan tersier. Pengumpulan data dilakukan secara wawancara, observasi, dan dokumentasi. Temuan penelitian menunjukkan bahwa faktor penyebab pernikahan sirri masyarakat Kecamatan Muara Bulian antara lain; karena tidak adanya restu dari orang tua, menghindari perbuatan dosa zina, dan untuk menghindari beban biaya administrasi. Di sisi lain, alasan masyarakat yang belum melaksanakan isbat nikah adalah karena faktor biaya. Seterusnya, tidak dapat dihindari bahwa terdapat pengaruh nikah sirri terhadap hak-hak isteri dan anak.